Life cycle assessment of solar communities. (1st September 2020) - Guarino, Francesco; Longo, Sonia; Hachem Vermette, Caroline; Cellura, Maurizio; La Rocca, Vincenzo
Highlights: Life cycle assessment comparative analysis of conventional/solar systems-based communities. The solar configuration includes solar thermal, PV, district heating with ground seasonal storage. Analysis of 1300 residential units and 21, 000 m 2 of commercial/institutional buildings in Okotoks (CA) The solar system has largely lower life cycle environmental impacts up to 79% for ozone depletion. Abstract: This study presents the comparison of the life cycle performance of two different urban energy systems, applied to a large mixed-use community, in Calgary (Canada). The two systems investigated consist of an energy efficient conventional system, using heat pumps for heating, cooling and domestic hot water; the second design widely deploys solar thermal panels coupled to district heating infrastructure and a borehole seasonal thermal storage. The analysis is based on the Life Cycle Assessment methodology and includes the stages of raw materials and energy supply, system manufacturing, use stage of the systems, generation and use of energy on-site, maintenance and components' substitution, and explores the performances of the systems on a life cycle perspective thanks to the use of different indicators of ILCD 2011 Midpoint impact assessment method. The solar-based system, performs better than the conventional system from the point of view of all indicators used in the study. In detail, ozone depletion and land use can be reduced of about 79.7% and 27% respectively, while the remaining impact categories show a reduction of about 39–56%. These results can be extended to other similar systems operating under similar weather constraints, energy systems included in the operation, thermal loads requirements. Moreover, the study is based on the premises and assumptions of real documented case studies in Canada, thus further reinforcing the solidity of the results.